Perceptions of canned wine drinkers in outdoor leisure settings: a vignette study with swiss residents - Nicolas Depetris Chauvin; Antoine Pinède; Heber Rodrigues (Wine Economics and Policy)
This study explores the prejudices of Swiss residents toward consumers of canned wine in the context of outdoor leisure activities. Despite the convenience and environmental benefits of canned wine, it faces resistance from wine consumers based on prejudices. We investigate whether holiday outdoor settings such as beach resorts, ski stations, desert safaris, and outdoor parties could mitigate these prejudices, as leisure contexts might reduce the ritualistic consumption patterns associated with wine drinking. Using a vignette study, Swiss residents evaluated the personality traits of canned wine consumers across different scenarios. Our findings reveal that, overall, canned wine drinkers are judged negatively, particularly in the beach resort scenario, where traits like “health consciousness” and “environmental friendliness” are rated lower. Demographic factors, including age, gender, and education, as well as cultural background, significantly influence these judgements. Younger respondents and expatriates showed less prejudice compared to older and more traditional Swiss residents, suggesting a generational and cultural divide in attitudes. These results underscore the need for targeted marketing strategies to address persistent stereotypes and foster a more positive image of canned wine among diverse consumer segments.